Edukasi rutin membaca 30 menit perhari meningkatkan fungsi kognitif lansia - Siti Munawaroh; Yunia Hastami; Adji Suwandono; Ari Natalia Probandari; Hartono; Fitriana Herawati; Ummu Ma'rifatul Afifah; Aldira Ayu Nastiti Nur Hanifah (ABDIMAS DEWANTARA, 2022)
Ageing is something that happens and cannot be avoided. The body's organs will decrease in function with age. The decline in the function of these organs results in a decrease in cognitive function in the elderly. Therefore, the elderly need to carry out cognitive activities regularly to maintain and improve their cognitive function of the elderly. One of the simple cognitive activities that can be done is reading. This community service aims to provide education to the elderly regarding routine reading that can improve cognitive function in the elderly. Methods: A total of 30 elderly in the Surakarta area were given direct education by the community service team face-to-face one-on-one. Then for two weeks, the elderly were controlled through social media to read at least 30 minutes per day. At the end of the activity, the elderly were asked to evaluate the activities carried out with seven questions answered on a Likert scale. The results of the evaluation given by the service participants to this activity were positive. The elderly feel the benefits of the service activities undertaken, including improving memory, helping to read fluently, increasing fluency in speaking, increasing interest in reading and increasing vocabulary. The conclusion is that a reading routine of 30 minutes per day positively impacts the elderly.